Quantification of aneurysm wall enhancement in intracranial fusiform aneurysms and related predictors based on high-resolution magnetic resonance imaging: a validation study - Fei Peng; Mingzhu Fu; Jiaxiang Xia; Hao Niu; Lang Liu; Xin Feng; Peng Xu; Xiaoyan Bai; Zhiye Li; Jigang Chen; Xin Tong; Xiaoxin He; et al. (Therapeutic Advances in Neurological Disorders, 2022)
Background: Aneurysm wall enhancement (AWE) in high-resolution magnetic resonance imaging (HR-MRI) has emerged as a new imaging biomarker of intracranial aneurysm instability. Objective: To determine a standard method of AWE quantification for predicting fusiform intracranial aneurysms (FIAs) stability by comparing the sensitivity of each parameter in identifying symptomatic FIAs. The predictors of AWE and FIA types were also identified. Methods: We retrospectively analyzed consecutive fusiform aneurysm patients who underwent HR-MRI from two centers. The aneurysm-to-pituitary stalk contrast ratio (CR stalk ), aneurysm enhancement ratio, and aneurysm enhancement index were extracted, and their sensitivities in discriminating aneurysm symptoms were compared using the receiver-operating characteristic curve. Morphological parameters of fusiform aneurysm were extracted based on 3D vessel model. Uni- and multivariate analyses of related predictors for AWE, CR stalk , and FIA types were performed, respectively. Results: Overall, 117 patients (mean age, 53.3 ± 11.7 years; male, 75.2%) with 117 FIAs underwent HR-MRI were included. CR stalk with the maximum signal intensity (CR stalk-max ) had the highest sensitivity in identifying symptomatic FIAs with an area under the curve value (0.697) and a cut-off value of 0.90. The independent predictors of AWE were aneurysm symptoms [(odds ratio) OR = 3.754, p  = 0.003], aspirin use (OR = 0.248, p  = 0.037), and the maximum diameter of the cross-section (OR = 1.171, p  = 0.043). The independent predictors of CR stalk-max were aneurysm symptoms (OR = 1.289, p  = 0.003) and posterior circulation aneurysm (OR = 1.314, p  = 0.001). Transitional-type showed higher rates of hypertension and mural thrombus over both dolichoectatic- and fusiform-type FIAs. Conclusion: CR stalk-max may be the most reliable parameter to quantify AWE to distinguish symptomatic FIAs. It also has the potential to identify unstable FIAs. Several factors contribute to the complex pathophysiology of FIAs and need further validation in a larger cohort.